Implementation of Sharia Maqashid in Household Financial Management: A Study on Women Members of the Aisyiyah Ponorogo Regional Leadership - Evilia Khoirun Nisa; Arif Hartono; Adib Khusnul Rois (Universitas Darunnajah, 2025)
This study examines the implementation of Maqashid Syariah principles in household financial management, focusing on women members of the Ponorogo Aisyiyah Regional Executive (PDA). The goal is to analyze financial practices, evaluate the application of Maqashid Sharia, and identify the role of Aisyiyah membership. This study uses a phenomenological qualitative approach by collecting primary data through in-depth interviews and observations of seven key informants who were purposively selected. The researcher analyzed the data through the stages of reduction, presentation, and conclusion verification. Key findings revealed that members implemented strategic financial management and aligned with the five goals of Maqashid Sharia. They diversify sources of income, prioritize spending (basic needs, religion, education), and invest in sharia instruments such as gold and land. The study also identifies mechanisms for operationalizing religious principles, such as the